THE ROLE OF THE MALAY LANGUAGE IN THE ISLAMIC HERITAGE OF ACEH - Nurul Rahmawaty; Eva Iryani; Dela Komalasari; Baginda Tua Heriansyah H; Titin Amelia (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2025)
The Malay language (Bahasa Melayu) played a crucial role in the development of Islam in Aceh, both as a lingua franca and as a medium for the transmission of knowledge through Jawi manuscripts. This study aims to analyze the profound contribution of the Malay language to the enrichment of religious, literary, and official Islamic documents in Aceh in the past. The research method employed is a qualitative approach using descriptive-analytical analysis. Data were collected through a literature review of ancient manuscripts and religious documents in the Malay language, and supplemented by in-depth interviews with historians and religious figures in Aceh. Data analysis involved data reduction, identifying patterns of language use within an Islamic context, and contextualizing these findings within the development of local culture. The results of the study indicate that the Malay language served as a cornerstone in the codification of Islamic teachings in Aceh. Its presence in classical religious texts proved to accelerate the diffusion and understanding of Islam among the people, while simultaneously integrating local scholarly traditions into the intellectual network of the Malay-Nusantara world. The majority of historical administrative documents and literary works discovered use this language, indicating the strong sociolinguistic influence of Malay within Aceh’s Islamic institutions. This study concludes that the Malay language is not merely a tool for transactional communication but a cultural artifact that shapes the intellectual identity of Islam in the region. Consequently, efforts to digitize, preserve, and re-examine ancient manuscripts written in Malay have become a matter of great urgency. This step is crucial for safeguarding the continuity of historical heritage and ensuring that the roots of Aceh’s Islamic heritage remain alive and continue to flourish in the future.